Eruptive hemangioma with satellitosis. Pathogenetic remarks concerning three pediatric cases. - Mazzotta, F.; Garofalo, L.; Caprio, F.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
The Authors report 3 children aged less than 10 years with satellitosis due to a primary eruptive hemangioma. The satellite lesions arise in 2 cases after surgical removal of the primary lesion and in 1 case a few months after the appearance of the primary lesion, which was still present. The satellite lesions are smaller, sometimes quite concentric and a few centimeters far from the primary lesion. On light microscopy, the satellite lesions are reminiscent of the primary one, namely consist of a neoformation of endothelial cells which tend to excavate a lumen in their inside. An epidermal collarette cannot be shown. The satellite lesions spontaneously regress within 9-16 months. Finally, the possible etiopathogenetic factors are discussed, taking into account the age of onset, the site most frequently involved and the present knowledge regarding the angiogenic factors.